METHODOLOGY PROPOSAL FOR CORRELATION STUDIES OF FLUVIAL SEDIMENTS BASED ON PETROGRAPHIC AND LITHOGEOCHEMICAL ANALYSIS: EXAMPLE OF ITS APPLICATION ON CENOZOIC ROCK FROM THE LISAMA FORMATION (MIDDLE MAGDALENA VALLEY, COLOMBIA) - Julián-Francisco Naranjo-Vesga; Pedro-David Gómez-Gutiérrez; Jaime-Ricardo Gélvez-Llanez; Noria-Elena Duque-Pardo; Néstor-Raúl Moreno-Gómez (CT&F Ciencia, Tecnología & Futuro, 2013)
ABSTRACT The petrographic and lithogeochemical analyses of fluvial sediments from the Lisama Formation suggest potential for the association of compositional and chemical changes of rocks with the identification and correlation of Cenozoic stratigraphic units in the Middle Magdalena valley basin. The integration of different compositional techniques enable the subdivision of the Lisama Formation into three petrographic zones. The zoning proposed herein match the palynological biozoning defined in the same stratigraphic sections, demonstrating their potential as a complementary correlation tool to biostratigraphy. This methodology of integrating petrographic and lithogeochemical analyses can be used in subsequent studies in the Middle Magdalena Basin, mainly in geographic areas where the palynomorph recovery is low or null. This work integrates Thin Section Analyses, Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and X-Ray Diffraction (XRD) in two correlatable outcrops in the Western and Eastern flanks of the Nuevo Mundo Syncline (NMS).